Manipulating Nb-doped SrFeO 3− δ with excellent performance for proton-conducting solid oxide fuel cells - Hailu Dai (19239613) (2024)
Nb-doped SrFeO3−δ (SFO) is used as a cathode in proton-conducting solid oxide fuel cells (H-SOFCs). First-principles calculations show that the SrFe0.9Nb0.1O3−δ (SFNO) cathode has a lower energy barrier in the cathode reaction for H-SOFCs than the Nb-free SrFeO3−δ cathode. Subsequent experimental studies show that Nb doping substantially enhances the performance of the SrFeO3−δ cathode. Then, oxygen vacancies (VO) were introduced into SFNO using the microwave sintering method, further improving the performance of the SFNO cathode. The mechanism behind the performance improvement owing to VO was revealed using first-principles calculations, with further optimization of the SFNO cathode achieved by developing a suitable wet chemical synthesis route to prepare nanosized SFNO materials. This method significantly reduces the grain size of SFNO compared with the conventional solid-state reaction method, although the solid-state reaction method is generally used for preparing Nb-containing oxides. As a result of defect engineering and synthesis approaches, the SFNO cathode achieved an attractive fuel cell performance, attaining an output of 1764 mW·cm−2 at 700 °C and operating for more than 200 h. The manipulation of Nb-doped SrFeO3−δ can be seen as a “one stone, two birds” strategy, enhancing cathode performance while retaining good stability, thus providing an interesting approach for constructing high-performance cathodes for H-SOFCs. Other Information Published in: Journal of Advanced Ceramics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.26599/jac.2024.9220880